2018
DOI: 10.1186/s12906-018-2358-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a proposed trial of acupuncture as an adjunct to lifestyle interventions for weight loss in Polycystic Ovary Syndrome: a qualitative study

Abstract: BackgroundPolycystic Ovary Syndrome (PCOS) is a common female reproductive disorder with multiple manifestations. Weight management is a key therapeutic goal. Acupuncture is a potential adjunctive weight loss treatment in non-PCOS populations. We aimed to engage patients in co-design and assess the feasibility and acceptability of methods for a randomised controlled trial (RCT) on acupuncture and telephone-based health coaching for weight management in overweight or obese women with PCOS using qualitative meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Our study methods have been previously described [25]. We conducted focus groups and semi-structured telephone interviews (offered to women through phone who were unable to attend the focus groups).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study methods have been previously described [25]. We conducted focus groups and semi-structured telephone interviews (offered to women through phone who were unable to attend the focus groups).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the aim of this study is to explore the experience of women with PCOS in weight management and to determine the facilitators and barriers to lifestyle modifications in women with PCOS. This investigation is part of a larger qualitative study that assessed the feasibility and acceptability of a method for an RCT on acupuncture and lifestyle for weight management in women with PCOS [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some small studies in this field have reported increased well-being as being associated with a sense of regained self-control (de Lacey et al, 2009;Rayner et al, 2009;Sointu, 2006), and similar findings have been reported by participants having acupuncture in other medical fields (Ee et al, 2018;McPherson et al, 2006;Paterson and Britten, 2004).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 55%
“…Electro-acupuncture reduced muscle sympathetic nerve activity in PCOS women in one trial [27]. Our qualitative work indicates high levels of acceptance of acupuncture as a possible adjunct to lifestyle interventions for weight loss [30].…”
Section: Introductionmentioning
confidence: 75%